Brazilian research on noninvasive brain stimulation applied to health conditions - Katia Nunes Sá; Gabriel Venas; Mayara Pinheiro de Souza; Daniel Ciampi de Andrade; Abrahão Fontes Baptista (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Brazil has a top position regarding scientific production on noninvasive neuromodulation worldwide. Knowledge of scientometric phenomena involving Brazilian researchers who produce science on this theme may aid confidence in Brazilian clinical and research professionals. Objective: To investigate the scenario of research on the theme of noninvasive neuromodulation in Brazil. Methods: This was a scientometric study for mapping scientific production on this subject involving network phenomena, the professions of researchers, institutional affiliation, main research unit, total number of scientific articles on noninvasive neuromodulation published in journals, research sub-area and year of obtaining the PhD title. Public data from Lattes Platform curricula vitae and from VOSViewer© were used. Results: A total of 54 Brazilian researchers were identified, of whom 16 are research productivity fellows. Most of them are linked to institutions in southeastern Brazil, involving the professions of biology, biochemistry, physical education, physiotherapy, speech therapy, gerontology, medicine and psychology, with 1175 articles published in journals. These studies involve experimental animal and human models to account for mechanisms, observational studies, case reports, randomized clinical trials, systematic reviews, meta-analyses, product and process development, computer modeling and guidelines. Conclusions: Brazil occupies a prominent place in the world scenario of research on noninvasive neuromodulation, which is used by different professions for treatment of brain dysfunctions, with a trend towards expansion to other fields.